Epistemological Obstacle on Triangle And Quadrilateral Topic - Fitri Anisa Kusumastuti; Muh. Khaedir Lutfi; Yusup Junaedi; Aliep (JURNAL PENDIDIKAN DAN SAINS, 2022)
One of the basic material in geometry is triangle and quadrilateral topic. It should be mastered by students before learning the next topic in geometry. In consequence, it becomes an essential topic. In fact, there are still students who have difficulties. That difficulties can be caused by learning obstacle during learning process. This discussion only focused on the students’ epistemological obstacle in learning triangle and quadrilateral topic. This study aims to identify the students’ epistemological obstacle based on errors when they answered the written test given. Five questions in written test were given to 25 grade VII students in one of junior high schools in Sumedang. This study used qualitative approach where data were analyzed with triangulation method from result of the test and the students’ interview. This research showed that the limitation of context in introducing triangles and quadrilateral was able to caused learning obstacle for the students. Furthermore, it caused the students having difficulty in solving the similar problem with different context in triangle and quadrilateral topic.